Moderators of Psychosocial Treatment for Pediatric Obsessive-Compulsive Disorder: Summary and Recommendations for Future Directions. Issue 4 (4th July 2021) - Kemp, Joshua; Barker, David; Benito, Kristen; Herren, Jennifer; Freeman, Jennifer
ABSTRACT: This brief report examines the evidence for moderators of psychosocial treatment for youth with obsessive-compulsive disorder (OCD). Understanding treatment moderators can help clinicians select the most appropriate intervention for a particular patient and consequently increase the likelihood of initial response. A systematic search of the literature was conducted to identify randomized trials and meta-analyses reporting on moderators of psychosocial treatment for pediatric OCD. All studies included a comparison of cognitive-behavioral therapy (CBT) to active or control conditions. Few studies have evaluated moderators of psychosocial treatment for youth with OCD, and among those studies, few variables have demonstrated a differential effect on treatment response. Moderator analyses require large samples to garner the statistical power necessary to adequately evaluate differential responding in subgroups, and unfortunately, most reports of moderators in this review are post-hoc investigations of datasets from trials with relatively small sample sizes. Given the overwhelming number of CBT treatment variants and potential moderators, it would be impossible to conduct all the necessary head-to-head trials with sufficient sample sizes to develop helpful clinical guidelines. The best option for advancing the moderator literature is to utilize advanced statistical approaches for pooling existing data sets. Recommendations for leveraging emerging techniques in individual participant data meta-analysis (IPD-MA) are briefly discussed.